If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -21 = x + 4 Reorder the terms: -21 + 2x = x + 4 Reorder the terms: -21 + 2x = 4 + x Solving -21 + 2x = 4 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -21 + 2x + -1x = 4 + x + -1x Combine like terms: 2x + -1x = 1x -21 + 1x = 4 + x + -1x Combine like terms: x + -1x = 0 -21 + 1x = 4 + 0 -21 + 1x = 4 Add '21' to each side of the equation. -21 + 21 + 1x = 4 + 21 Combine like terms: -21 + 21 = 0 0 + 1x = 4 + 21 1x = 4 + 21 Combine like terms: 4 + 21 = 25 1x = 25 Divide each side by '1'. x = 25 Simplifying x = 25
| x^2+17=19 | | 40x-18(x-3)=468 | | y+6.2=9.1 | | 63=c-21+2c | | 3/6=/8 | | 16+x=42 | | 3.29-0.223= | | 4t^2-20t-60=0 | | 2sin(30+x)=3cosx | | 2+p=2 | | 5n-6=7 | | ln(x)+ln(1.1675x)=5.28 | | 5x-6=93-6x | | 5t+4=11 | | -14=x/2 | | (3x-9)(2x-2)= | | 4.500+60v=50(100+v) | | 4(13-y)+2y=36 | | -42+14x=4y | | 3y+2x-7+12-6x+4y=56-45x+2y | | (c+2)=5(c+1)-7 | | n-3=1 | | -5v=-5 | | 32+(-16)+(-12)= | | 2(c+2)=5(x+1)-7 | | -3x^4+5x^3-2x^2+9=0 | | y=3x^5-4x^2+2 | | 3/5n=6 | | 3y-8+6x= | | (3x^2-2x+4)-(-5x^2+3x-8)= | | 11v-12/v-5 | | 5x+7y=19fory |